Studies in macroeconomics and welfare/edited by B. B. Bhattacharya and - "Bhattacharya, B. B. (ed.)" (New Delhi, 2005)
Selected papers contain studies on exchange rate, interest rate, money demand and supply, monetary and fiscal policies, inflation and its relationship with growth at aggregate and sectorial levels, growth and distribution, pollution, environment, rural poverty, health care and micro credit.
Keywords: macroeconomics